Challenges of Banking Profitability in Eurozone Countries: Analysis of Specific and Macroeconomic Factors - A. Durguti, Esat (Naše gospodarstvo/Our economy, 2022)
Numerous factors affect the rate of return that a financial institution earns. Some of these factors include external forces that shape earnings performance and internal elements found in each financial institution. Policy implications are determined by the type of explanation and should be taken seriously. This paper classifies determinants of bank profitability as well as reviews existing literature on bank performance. The second section of this study quantifies how external factors and internal determinants have influenced the profitability of EU banks. This paper constructs fixed-effect models and Ordinary Least Squares (OLS), which sheds new light on understanding various factors influencing how the EU banking industry performs. The observation period was from 2012 to 2019, and the findings revealed that EU bank profitability is influenced by both external macroeconomic environment and management decisions. The results of this study suggest that equity to assets ratio (EA), Gap ratio, and GDP have a positive impact on bank profitability, while the loan to assets ratio (LA) and the provision for loan losses to total loans ratio (PLL/TL) hurt EU bank profitability. The empirical findings are consistent with the expected results, although, they are different from those of studies that investigated the structure-performance relationship of EU banks because they found that market share and concentration have a positive effect on bank profitability.